Análisis del proceso de implementación de la presencialidad asistida por tecnologías de la información y comunicación (TIC ́S) en la Fundación Universidad de América, durante la pandemia covid-19 (2022)
The purpose of this degree work is to analyze the implementation process of the virtual methodology implemented in the Universidad de América Foundation due to the contingency presented since 2020 by COVID 19. Taking into account that classes are the main environment of learning in which an education service is provided whose modality is face-to-face and allows students and teachers to see their classes in a physical way and meet academic expectations, it is of the utmost importance to analyze how effective the adaptation process was to the new virtual methodology.